2016
DOI: 10.7554/elife.11878
|View full text |Cite
|
Sign up to set email alerts
|

Ceapins are a new class of unfolded protein response inhibitors, selectively targeting the ATF6α branch

Abstract: The membrane-bound transcription factor ATF6α plays a cytoprotective role in the unfolded protein response (UPR), required for cells to survive ER stress. Activation of ATF6α promotes cell survival in cancer models. We used cell-based screens to discover and develop Ceapins, a class of pyrazole amides, that block ATF6α signaling in response to ER stress. Ceapins sensitize cells to ER stress without impacting viability of unstressed cells. Ceapins are highly specific inhibitors of ATF6α signaling, not affecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
120
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(129 citation statements)
references
References 62 publications
(99 reference statements)
8
120
0
1
Order By: Relevance
“…Additionally, FLI-06 hindered DHC-induced ATF6 from appearing in the nucleus, just as it had for Tg-induced ATF6 (Figure 4F). In a further similarity, treatment of cells with Ceapin A7, an inhibitor of Tg activation of ATF6 (Gallagher et al, 2016; Gallagher and Walter, 2016), also blocked DHC activation of ATF6 (figure 4C–4E, S4B, and S4C). Lastly, we asked whether DHC activation must induce cleavage of the transmembrane domain of ATF6 for effective activation (freeing of the N-terminal transcription factor domain).…”
Section: Resultsmentioning
confidence: 67%
“…Additionally, FLI-06 hindered DHC-induced ATF6 from appearing in the nucleus, just as it had for Tg-induced ATF6 (Figure 4F). In a further similarity, treatment of cells with Ceapin A7, an inhibitor of Tg activation of ATF6 (Gallagher et al, 2016; Gallagher and Walter, 2016), also blocked DHC activation of ATF6 (figure 4C–4E, S4B, and S4C). Lastly, we asked whether DHC activation must induce cleavage of the transmembrane domain of ATF6 for effective activation (freeing of the N-terminal transcription factor domain).…”
Section: Resultsmentioning
confidence: 67%
“…To determine whether the effects of AA147 on hESC differentiation required ATF6 activation, we treated hESCs with the small-molecule ATF6 inhibitor, Ceapin-A7 (38). Ceapin-A7 inhibits ATF6 signaling by trapping the full-length ATF6 molecule in the ER, thereby preventing the generation of ATF6(N) transcriptional activator (39).…”
Section: Resultsmentioning
confidence: 99%
“…The current therapeutic and pharmacological strategies that target ER proteostasis in cancer focus either on exacerbating ER stress to a level with which tumor cells cannot cope and therefore die or on decreasing the adaptive capacity of the tumor cells, leading to loss of selective advantage and tumor death. Over the past 5 years, several inhibitors of the three UPR sensors have been developed (Table 1) (44,58,(126)(127)(128)(129)(130)(131)(132)(133)(134)(135)(136)(137)(138)(139)(140). Some new drugs are now tested to specifically target particular UPR sensors to kill cancer cells or sensitize them to commonly used treatments.…”
Section: Er Proteostasis Control and Response To Chemotherapy And Radmentioning
confidence: 99%
“…The protein disulfide isomerase PDIA5 is critical for ATF6 activation, enabling its export from ER under stress conditions; genetic or pharmacological inhibition of the PDIA5/ATF6 axis (using the PDI inhibitor 16F16) sensitizes leukemia cells to imatinib treatment (58). Similarly, in a more recent work, it was demonstrated that ceapins, a class of pyrazole amides, blocked ATF6 signaling in response to ER stress by trapping it in the ER (126,127). On the other hand, Plate et al identified two nontoxic small molecules, compounds 147 and 263, which selectively activated the ATF6 branch of the UPR (128).…”
Section: Er Proteostasis Control and Response To Chemotherapy And Radmentioning
confidence: 99%